PERAMALAN KEBUTUHAN ENERGI LISTRIK TAHUN 2006-2015 MENGGUNAKAN METODE GABUNGAN DENGAN PEMROGRAMAN VISUAL BASIC - Nugroho, Agung; Winardi, Bambang (Transmisi, 2008)
Forecasting d ernandi s an activity that must be provided in the first time in electricsle nerg/ developmentt o get economicallyin elqctricale nergyg enerationa nd its distribution. P.T. PLN the Indonesianp ublic electricale ner$/ provido for fore.astingd emandu se an hybdd method include sectohl alFoacb in econometric (economical growing), treDd (ithabitant growilg), and anal)tic, In this method the electrical eners/ customsis were groupedin to 4 sectorsh ome,b usinessp, ublic, andi ndustry. The last 5 yearsd atao f tho 4 sectoragl rowingd 6t! wereu seda ndt he forecastingta rgets are eoerry con$unptionp rcdiction( in MWh), cormâ‚¬ctedp ower( in KVA), the numbero f cu.stometro, tal etrergyd emardt hatm ustb e produced( in MWh), andp eakl oading( MW). ln this research sooekind of applicatiofl progam usi.g Visual Basic to oalculate and analysist he forecastingd emandw asm adea ndf or studyc aset he dataa re ftom P.T. PLN UPJ( Unit PelayanoJns dngan)B oyolali area. Â  Keywords: foreclsting electricol ercrgy demao4 hybrid method